Linguistic Features and Foregrounding Aspects in Dylan Thomas’ “We Lying by Seasand”: A Stylistic Analysis (Raparin Journal of Humanities (RJH), 2024)
The main difficulty in understanding Thomas’ poetry is his diction and style, which the reader usually relies on to comprehend his poems. It would be difficult to go through character, activity, situation, or anything else unless the reader is able to grasp their sense. Thomas wrote many great poems. The selected poem is among these difficult and great poems. An obvious way to remove these obstacles is to depend on the use of linguistic features and the foregrounding theory of stylistics to explicate his poem. For this purpose, the present study is also supplemented by the checklist of Leech and Short (2007) to identify, describe, and evaluate the linguistic categories of the poem while making use of literary interpretations. As a result, the study is based on a qualitative descriptive analysis, which is used first to investigate the specific types of parallelism and deviations in the poem, then through describing and evaluating them the study shows how these prominent features help understanding and highlighting the themes and meaning behind the words. The study finds out that being able to identify and relate the prominent linguistic aspects supports the reader’s explications of this poem.